The Islamic legal remedy on husband's imprisonment - Tengku Muda, Tengku Fatimah Muliana; Mohd, Azizah; Md Hashim, Noraini; Wan Mohd Khairudin, Wan Mohd Khairul Firdaus; Syed Husin, Syh Noorul Madihah; Mohd Yusoff, Zurita (Allied Business Academies, 2019)
The need of a prisoner’s wife is often not an issue of concern for many. Despite financial struggle, the imprisonment of the husband may affect the wife’s emotional being and inner needs. Since the repulsion of harm (mafsadah) serves as the objective of Islamic legal rulings, this paper seeks to examine the juristic views of different schools of laws in Islam on the remedy available where the husband has been sentenced for imprisonment. For comparative purpose, the provisions of law related to husband’s imprisonment as applied in Malaysia, Jordan, Egypt and Morocco are also discussed. Using content analysis method, the findings indicate that where the husband has been imprisoned, dissolution of marriage is allowed based on the ground of protecting the interest of the spouse, as well as an appraisal to the Islamic principle of repulsion of harm.